TINJAUAN YURIDIS TERHADAP PERJANJIAN ANJAK PIUTANG PADA LEMBAGA PEMBIAYAAN BANK DI SAMARINDA - Gladys Chalista Shilvadara (Journal of Law ( Jurnal Ilmu Hukum ), 2013)
ABSTRACTImpractical provisions of article 613 of the Civil Code regarding notification megakibatkan particular client does not want to require notification to the debtor. The client only requires that the factor will purchase receivables or the bills without any obligation to require notification to the debtor. Accounts receivable financing facility and factoring agreement, so memungkingkan mestipun client to transfer receivables from debtors without notification. However, not all clients can mengalih receivables / bills-bills without notification of the debtor, but only tertentulah clients who can use the facility accounts receivable financing and factoring agreement based on considerations about the client's personal factors.While the legal consequences of the factoring agreement is not complied with the provisions of Article 613 KUPerdata are as follows: Failure to use the provisions of Article 613 of the Civil Code, especially regarding notification factoring agreement resulted in the debtor is not bound to the factoring agreement made by the lien dank factor. This is in accordance with the provisions of article 1340 of the Civil Code which states: The agreements apply only to those who make it. The agreements were tidadak can bring loss on third parties, no third parties can benefit, therefore, in others in the case provided for in Article 1317 of the Civil Code; Not used the provisions of article 613 of the Civil Code in the factoring agreement gives a very high risk to the factor, both in terms of legal and commercial terms. Olehkarena to protect himself from the things that may be harmful, then factor always ask for a guarantee from the client. With the guarantee of the factoring activity, it can be seen that the activity of pure factoring company, but has led to the activities of banking institutions. Therefore, factoring companies are no longer able to dikatakanh as an alternative financial institution after the bank, but it is a major competitor of banking institutions; Failure to use the provisions of article 613 of the Civil Code in particular regarding notification factoring agreement is not a factoring agreement as provided for in Presidential Decree No. 16 In 1989 Jo Minister of Finance Decree 1251 / KMK.013 / 1989 but only as a loan agreement to borrow money with the guarantees given by the client. Therefore an agreement to borrow money using the name of the factoring is null and void.